PENGARUH BAHAN TAMBAHAN KE DALAM MEDIA VACIN DAN WENT TERHADAP PERKEMBANGAN ANGGREK Dendrobium sp - Zunaidi, Mahbub; Astutik, Astutik; Sumiati, Astri; Agastya, I Made Indra (BUANA SAINS, 2024)
The research aimed to determine the effects of the potato and banana extract supplements in fresh form and flour with different measurements on the growth of plantlet orchid Dendrobium sp in vitro. Factorial Random Planning (RAL) consists of two factors: type of additive and measurement against 16 combinations of treatments, and five repetitions. In total, there are 320 samples of plants. Observations included the percentage of live plantlets, the start time of the shoots, the shoot height, the number of leaves, the root initiation time, the root number, and the root length. The results of the study showed that there was an interaction between the type of additive and the mark against the percent of living plantlets at age 4, 8, and 12 weeks, the height of shoots at age 8 and 12, the root initiation times, the count of roots and the length of the root. The growth percentage ranges from 80-100%, except for the potato flour additive 200 g/l of 45%. Potato and banana additives in the form of flour can increase the start time of the shoots faster than in the fresh form.